Sarcoidosis Manifested as Recurrent Pericardial Effusion with Signs of ImpendingTamponade - Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2021)
Pericardial effusion is a fatal and life-threatening condition. If it is not addressedthoroughly, complications such as constrictive pericarditis may occur. Etiologies ofpericardial effusion varied and one of the most common etiologies is tuberculosis.Other etiologies include inflammation, malignancy or other autoimmune disordersuch as sarcoidosis. Sarcoidosis is a diagnosis of exclusion and is confirmed bybiopsy result that showed non-caseating epitheloid-cell granuloma, with no otherorganism or particles. Epidemiology of sarcoidosis in Japan is 1-2 case per 100.000patients, with the peak incidence between the age of 20 to 39 years old. We reporteda case of 37 years old woman presented to our emergency department withshortness of breath and signs of pericardial tamponade. She was previously healthywith no other significant past medical. She was first treated as a case ofextrapulmonary tuberculosis and shown no improvement with anti-tuberculosismedications. Several work ups were then done in search of other etiologies of herpericardial effusion. A biopsy form one of her abdominal lymph nodes wasperformed, which pathologically revealed sarcoidosis. She was placed oncorticosteroid and methotrexate with improvement of symptoms. One monthfollowed up showed complete resolution of her pericardial effusion.